How UK HE STEM Students Were Motivated to Switch Their Cameras on: A Study of the Development of Compassionate Communications in Task-focused Online Group Meetings - J. M. P. V. K. Jayasundara; Theo Gilbert; Saskia Kersten; Li Meng (Education Sciences, 2022)
HE’s pandemic-driven shift to online platforms has increased social and learning disconnection amongst students. In online group work/teamwork, many are reluctant to switch on their cameras to be more present to others. Compassion in group work/teamwork is defined as noticing, not normalizing, one’s own and/or others’ distress or disadvantaging and taking wise action to prevent or reduce this. This notion of compassion is being assessed in the HE sector using filmed task-focused in-class group work meetings to identify levels of both inclusivity and criticality around the team. This study investigates the use and outcomes of using the compassionate communications strategies (that were developed in and for the offline classroom) in online team meetings. In this mixed-methods study, two groups of four international STEM students, each from a sample of five UK universities, were video-recorded in task-focused group work meetings (TGMs) before and after an online interactive 90-min training session (‘the intervention’) on the Cognitive Skills of Compassionate Communications (CSCC) in teams. A comparison of the (pre and post CSCC intervention) quantitative and qualitative data results indicated, post-intervention, a significant increase in students’ screen gaze attentiveness to each other, and reasons why students’ motivation to switch on their cameras had changed.